1999
DOI: 10.1007/s004399900075
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of lysosomal storage diseases in The Netherlands

Abstract: We have calculated the relative frequency and the birth prevalence of lysosomal storage diseases (LSDs) in The Netherlands based on all 963 enzymatically confirmed cases diagnosed during the period 1970-1996. The combined birth prevalence for all LSDs is 14 per 100,000 live births. Glycogenosis type II is the most frequent LSD with a birth prevalence of 2.0 per 100,000 live births, representing 17% of all diagnosed cases. Within the group of lipidoses, metachromatic leukodystrophy (MLD) is the most frequent LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
432
4
24

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 641 publications
(476 citation statements)
references
References 14 publications
16
432
4
24
Order By: Relevance
“…3.2.1.22). The estimated birth prevalence has originally been reported to be between 1:40.000 and 170.000 (Meikle et al 1999;Poorthuis et al 1999;Desnick et al 2007). More than 600 variants/mutations in the a-galactosidase A (GLA) gene have been described (Garman 2007;HGMD 2014), most of which are private variants/mutations.…”
Section: Introductionmentioning
confidence: 99%
“…3.2.1.22). The estimated birth prevalence has originally been reported to be between 1:40.000 and 170.000 (Meikle et al 1999;Poorthuis et al 1999;Desnick et al 2007). More than 600 variants/mutations in the a-galactosidase A (GLA) gene have been described (Garman 2007;HGMD 2014), most of which are private variants/mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion b-Mannosidosis is an extremely uncommon lysosomal storage disease with an estimated incidence of 0.1 per 100,000 (Poorthuis et al 1999;Poupetova et al 2010). It results from a deficiency in the activity of the lysosomal enzyme b-mannosidase which cleaves the unique b(1-4)-linked mannose sugar found in all N-linked oligosaccharides of glycoproteins (Thomas 2001).…”
Section: Case Reportmentioning
confidence: 99%
“…Estimates of MPS VI incidence range from 1 in 238,095 to 1 in 1,300,000 in the Netherlands (Poorthuis et al 1999); even higher rates have been reported in Portugal and Brazil (Valayannopoulos et al 2010). This lysosomal disorder, caused by a deficiency in the enzyme N-acetylgalactosamine-4-sulfatase (arylsulfatase B, ASB; EC 3.1.6.12), is a result of mutations in the arylsulfatase B gene (ASB) located on chromosome 5 (5q13-5q14) (Litjens et al 1989).…”
Section: Introductionmentioning
confidence: 99%